Epigenetic meta-analysis across three civilian cohorts identifies NRG1 and HGS as blood-based biomarkers for post-traumatic stress disorder. (20th November 2018) - Uddin, Monica; Ratanatharathorn, Andrew; Armstrong, Don; Kuan, Pei-Fen; Aiello, Allison E; Bromet, Evelyn J; Galea, Sandro; Koenen, Karestan C; Luft, Benjamin; Ressler, Kerry J; Wildman, Derek E; Nievergelt, Caroline M; et al.
Aim: Trauma exposure is a necessary, but not deterministic, contributor to post-traumatic stress disorder (PTSD). Epigenetic factors may distinguish between trauma-exposed individuals with versus without PTSD.Materials & methods: We conducted a meta-analysis of PTSD epigenome-wide association studies in trauma-exposed cohorts drawn from civilian contexts. Whole blood-derived DNA methylation levels were analyzed in 545 study participants, drawn from the three civilian cohorts participating in the PTSD working group of the Psychiatric Genomics Consortium.Results: Two CpG sites significantly associated with current PTSD in NRG1 (cg23637605) and in HGS (cg19577098).Conclusion: PTSD is associated with differential methylation, measured in blood, within HGS and NRG1 across three civilian cohorts.